Concepts and realities of family farming in Asia and the Pacific - Jingzhong Ye; Lu Pan (International Policy Centre for Inclusive Growth (IPC-IG), 2016)
The Asia and the Pacific region has the largest number of family farms in the world. It is home to 60 per cent of the world's population and to 74 per cent of the world's family farmers, with China alone representing 35 per cent and India 24 per cent of the estimated 570 million farms worldwide (Lowder et al. 2014). Though generally working in small plots of less than 2 hectares on average, family farmers in Asia and the Pacific produce 80 per cent of the total food needed to ensure food security in the region (AFA 2014). It is undeniable that family farming has played a central role in the socio-economic development and well-being of the entire population of Asia and the Pacific. As the reports for the Food and Agriculture Organization of the United Nations (FAO) Regional Conference for Asia and the Pacific stated, 'family farming is essential for the sustainability of agricultural, forestry and fishery production systems... (family farms) are the context in which important decisions on natural resource management are made. They hold the key to achieving food security not only for themselves, but also for the increasingly large number of families that have left the farm sector for employment in other occupations. [...]
Keywords: 330; concepts; realities; family farming; Asia; Pacific